THE USE OF SKIMMING TECHNIQUE IN STUDENTSâ READING COMPREHENSION - Rusmiati, Rusmiati; Ghafura, Arsyi (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
Reading is a greatly necessary expertise to comprehend by English language learners. It is the ability to recognize the meaning from a text as intended by the writer. The reason for teaching reading to the students is because it belongs to the basic language skill in English. Students are expected to be able to read text book written in English because it is a foreign language for Indonesian students. It means that to understand the materials, the students must have the ability to look at and get the meaning of written text. Therefore, reading is very important to teach to students. This study aimed to find out whether the use of skimming technique in studentsâ reading comprehension is effective. The population of the study was 26 students, so all of them were used as the sample. The study was quantitative method which applies statistical formula in analyzing the data. The finding showed that skimming technique improved studentsâ reading comprehension. It can be seen from the result of t-test and t-table. The former is 12,087 and the latter is 2,06. As t-test was greater than t-table, it can be concluded that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Ha states that skimming technique improves studentsâ reading comprehension.Keywords: reading comprehension, skimming technique